2016
DOI: 10.1016/j.jep.2016.05.045
|View full text |Cite
|
Sign up to set email alerts
|

Functional proteomic analysis revels that the ethanol extract of Annona muricata L. induces liver cancer cell apoptosis through endoplasmic reticulum stress pathway

Abstract: Our results indicate that the ethanol extract of leaves of Annona muricata L. causes apoptosis of liver cancer cells through ER stress pathway, which supports the ethnomedicinal use of this herb as an alternative or complementary therapy for cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 26 publications
0
47
0
3
Order By: Relevance
“…For example, extracts of Annona muricata can cause apoptosis of cancer cells and inhibit tumor growth through the activation of ERS pathway, with the upregulation of GRP94, HSP70, Bip and CHOP, as well as the upregulated phosphorylation of PERK and eIF2α [32]. Andrographolide induces apoptosis of colon cancer cells via the upregulation of ERS proteins GRP78, CHOP as well as the decreased BAX/Bcl-2 ration [33].…”
Section: Discussionmentioning
confidence: 99%
“…For example, extracts of Annona muricata can cause apoptosis of cancer cells and inhibit tumor growth through the activation of ERS pathway, with the upregulation of GRP94, HSP70, Bip and CHOP, as well as the upregulated phosphorylation of PERK and eIF2α [32]. Andrographolide induces apoptosis of colon cancer cells via the upregulation of ERS proteins GRP78, CHOP as well as the decreased BAX/Bcl-2 ration [33].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the mechanism of action revealed that growth‐inhibition activity is associated with the disruption of membrane mitochondrial potential, ROS generation, and G 0 /G 1 cell arrest. An involvement of the apoptotic pathway was also identified for A. muricata in liver cancer Hep G2 cells . The extract reduced cell viability and elicited apoptosis via the upregulation of HSP70, GRP94, and DPI‐related protein 5 expression.…”
Section: Extracts From Annona Speciesmentioning
confidence: 84%
“…An involvement of the apoptotic pathway was also identified for A. muricata in liver cancer Hep G2 cells. 12 The extract reduced cell viability and elicited apoptosis via the upregulation of HSP70, GRP94, and DPIrelated protein 5 expression.…”
Section: Extracts From Annona Speciesmentioning
confidence: 97%
“…A. muricata is used for curing hypertension, headaches, fever, rheumatism, diabetes, insomnia, parasite infection, diarrhea, dysentery and many more conditions [26,31]. Extract of A. muricata leaves is used as an alternative therapy for cancer as it causes apoptosis of the liver cancer cells [32]. Likewise, T. indica is used for abdominal pain, wound healing, constipation, inflammation, respiratory problems, diarrhea and dysentery [25,27,33].…”
Section: Introductionmentioning
confidence: 99%